Efektivitas Ketentuan Pasal 2 UUPerkawinan Tentang Perkawinan Beda Agama di Indonesia (Studi Kasus Perkawinan Beda Agama di Indonesia) - Lessnussa, Leony Valentina; Hadiati, Mia (UNES Law Review, 2023)
The legitimate of a marriage is clearly stated in the Marriage Law No.1 1974 in article 2, it is declared valid if it is carried out according to the laws of each religion and belief and must be recorded according to the applicable laws and regulations, but then there are other rules contained in the Administration Law No.23 2006 Article 35 states that marriages that occur because of differences in religion are still recorded in the civil registry. This research uses normative (doctrinal) methods. Meanwhile, there are problems related to the legal status arising from interfaith marriages which are registered based on court decisions, so that it becomes a legal issue, but currently the Supreme Court has issued a circular stating that judges in adjudicating such matters will not do so. grant the application for marriage registration submitted at a later day.